Incremento de áreas impermeables por cambios de usos de la tierra en la microcuenca del río Burío - Masís Campos, Ramón (2014)
Three scenarios were analyzed to show by changes of land use in the years 1960, 1990 and 2010.The results demonstrated a replacement rural covers for urban development. The impervious surfaces have altered the hydrological response watershed for the ability of the surface to promote or hinder direct runoff, infiltration of water or interception. This has resulted in increased peak flows in a watershed.